Factors associated with dysmenorrhoea and menorrhagia improvement in patients with adenomyosis after uterine artery embolisation - Siqi Hu; Wenbo Guo; Song Chen; Zhiqiang Wu; Wenquan Zhuang; Jianyong Yang (Journal of Obstetrics and Gynaecology)
Background This study examined the improvement of dysmenorrhoea and menorrhagia after uterine artery embolisation (UAE) in women with symptomatic adenomyosis and identified factors that could predict the improvement of dysmenorrhoea and menorrhagia.Methods This retrospective study included women with adenomyosis who underwent bilateral UAE between December 2014 and December 2016. The percentage of the volume of the absence of contrast enhancement on T1-weighted images was evaluated 5–7 days after UAE. A receiver operating characteristic (ROC) analysis was used to determine a cut-off point and predict the improvement of dysmenorrhoea and menorrhagia.Results Forty-eight patients were included. At 24 and 36 months after UAE, the improvement rates for dysmenorrhoea and menorrhagia were 60.4% (29/48) and 85.7% (30/35), and the recurrence rates were 19.4% (7/36) and 9.1% (3/33), respectively. Only the percentage of the volume of the absence of contrast enhancement on T1-weighted images was associated with the improvement of dysmenorrhoea (p = 0.001, OR = 1.051; 95% CI: 1.02–1.08) and menorrhagia (p = 0.006, OR = 1.077; 95% CI: 1.021–1.136). When the cut-off value of the ROC analysis was 73.1%, sensitivity, specificity, positive predictive value, and negative predictive value for the improvement of dysmenorrhoea were 58.6%, 94.7%, 94.4%, and 60%, while they were 58.9%, 80%, 100%, 100%, and 45.5% for the improvement of dysmenorrhoea.Conclusion Bilateral UAE for symptomatic adenomyosis led to good improvement of dysmenorrhoea and menorrhagia. The percentage of the volume of the absence of contrast enhancement on T1-weighted images of the uterus in postoperative magnetic resonance imaging might be associated with the improvement of dysmenorrhoea and menorrhagia.